2006
DOI: 10.1021/es0600577
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of Mercury(II) in Soil Organic Matter:  EXAFS Evidence for Linear Two-Coordination with Reduced Sulfur Groups

Abstract: The chemical speciation of inorganic mercury (Hg) is to a great extent controlling biologically mediated processes, such as mercury methylation, in soils, sediments, and surface waters. Of utmost importance are complexation reactions with functional groups of natural organic matter (NOM), indirectly determining concentrations of bioavailable, inorganic Hg species. Two previous extended X-ray absorption fine structure (EXAFS) spectroscopic studies have revealed that reduced organic sulfur (S) and oxygen/ nitrog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
286
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 364 publications
(315 citation statements)
references
References 42 publications
28
286
0
1
Order By: Relevance
“…This is consistent with previous reports of organics, and more especially of reduced sulfur groups, being the most effective sorbents for Hg in acidic environments (pH < ~4.5-5.0), compared to iron oxides and clay minerals (Andersson, 1979;Schuster, 1991;Roulet and Lucotte, 1995;Skyllberg et al, 2000;Skyllberg et al, 2006;Manceau and Nagy, 2008 values. This observation is consistent with the strong affinity of Hg(II) for gibbsite (Kim et al, 2004a;Kim et al, 2004b;Weerasooriya et al, 2007).…”
Section: Hg Carrier Phases In Soil Profilessupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous reports of organics, and more especially of reduced sulfur groups, being the most effective sorbents for Hg in acidic environments (pH < ~4.5-5.0), compared to iron oxides and clay minerals (Andersson, 1979;Schuster, 1991;Roulet and Lucotte, 1995;Skyllberg et al, 2000;Skyllberg et al, 2006;Manceau and Nagy, 2008 values. This observation is consistent with the strong affinity of Hg(II) for gibbsite (Kim et al, 2004a;Kim et al, 2004b;Weerasooriya et al, 2007).…”
Section: Hg Carrier Phases In Soil Profilessupporting
confidence: 92%
“…In particular, the relative proportions of soil components responsible for Hg retention [clay minerals, Fe-, Al-, and Mn-(oxyhydr)oxides, organic matter] vary with the geochemical conditions which in turn depend on the topographic position along the soil association (Boulet et al, 1993;do Valle et al, 2005;Fritsch et al, 2005;Fritsch et al, 2006). Hg has a high affinity for soil organic matter, especially for reduced sulfur groups such as thiol ligands (Schuster, 1991;Skyllberg et al, 2000;Khwaja et al, 2006;Skyllberg et al, 2006). High Hg levels can also be associated to Fe-(oxyhydr)oxides.…”
Section: Introductionmentioning
confidence: 99%
“…B-horizon during pedogenesis (Boyle and Jonasson 1973;SCWG 1998). The strong enrichment of Hg in humus results from the atmospheric deposition of Hg from local and distal sources, as well as gaseous Hg flux from underlying soils, and the subsequent bonding of Hg to thiol groups in soil organic matter (Grigal 2003;Skyllberg et al 2006). As expected, the concentrations of both As and Hg are lowest in the Ae horizon at most sample sites, reflecting the leaching of soluble constituents during soil formation and their transport to deeper horizons.…”
Section: Field Observationssupporting
confidence: 52%
“…The significant correlation between Hg concentration and SOM, humic acids, CEC, and amorphous iron oxides suggested that chelated with humic substance and specifically adsorbed to the hydrous ferric oxides (HFO) might be the dominant mechanisms of Hg sequestration in soils of the YRD and the PRD. Mercury exhibits a great affinity for organic matter in soils by forming complexes with reduced sulfur groups (Skyllberg et al 2006; Feo (mg/kg) Fig. 3 Linear regression between the measured Hg concentrations and topsoil properties.…”
Section: Soil Pools Of Anthropogenic Hgmentioning
confidence: 99%
“…Besides being affected by anthropogenic sources, accumulation of Hg in soil also depends on soil properties such as soil organic matter (SOM) content, pH, and cation exchange capacity (CEC) (Huang et al 2011;Smith-Downey et al 2010;Yang et al 2007). It has been well known that Hg has a high affinity for organic matter in soil and sediment (Ravichandran 2004;Skyllberg et al 2006;Wallschlager et al 1998). Mercury therefore tends to be retained in soils although losses do occur by leaching and volatilization (Grigal 2002;Scholtz et al 2003).…”
Section: Introductionmentioning
confidence: 99%